THE RELATIONSHIP BETWEEN WAIST CIRCUMFERENCE AND HBA1C LEVELS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS AT JIMBUN MEDIKA PRIMARY CLINIC - Berliana Puspita; Dian Estiningtyas (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2026)
Type 2 diabetes mellitus (T2DM) is a chronic metabolic disease associated with long-term macrovascular and microvascular complications. Glycated hemoglobin (HbA1c) is widely used as an indicator of long-term glycemic control, whereas waist circumference reflects central obesity, which is closely related to insulin resistance. This study aimed to analyze the relationship between waist circumference and HbA1c levels among patients with T2DM enrolled in the Chronic Disease Management Program (Prolanis) at Jimbun Medika Primary Clinic, Kediri. This study used an analytical observational design with a cross-sectional approach. A total of 17 respondents were selected using purposive sampling based on predetermined inclusion and exclusion criteria. Waist circumference was measured using a non-elastic measuring tape, while HbA1c data were obtained from laboratory records within the last three months. Data were analyzed descriptively and using correlation analysis. Pearson correlation was used when the data were normally distributed, while Spearman correlation was used when the data were not normally distributed. The results showed that all respondents had waist circumference above the central obesity threshold and HbA1c levels above 7%, indicating poor glycemic control. Due to the small sample size and the absence of variation in categorical data, the findings should be interpreted as preliminary evidence. This study concludes that waist circumference may be used as a simple anthropometric indicator to support the assessment of glycemic control in patients with T2DM. Further studies with larger sample sizes and more varied data are recommended.